(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
This paper shows that assembling thought as well as actor-network theory (ANT) have such a great deal in common than the debate suggests. It proposes three cross-fertilizations depending on intersections as well as disjunctions among the two techniques, with implications for comprehending three key socio-material processes: stability, transformation, as well as affect. To begin with, ANT’s conceptual language may aid assemblage thinking by offering a spatial account of how aggregates are brought collectively, extended over space, and stabilize. Secondly, each technique is better adapted to thinking about a certain type of variation in socio-material interactions: ANT depicts change without rupture (fluidity), whereas assemblage thinking depicts change with rupture (events). Finally, assemblages thought has the ability to instil in ANT a greater understanding of affect’s generative role in the construction of socio-material links through the establishment of desire/wish. We demonstrate the implications of this cross-fertilization for empirical studies through a case study of the global market for assisted reproduction.